Is Altruism be The Main Reason for Education Students to Become Teachers? With Gender and Culture as Moderating Variables - Arrahmah, Nabilah; Mintasih Indriayu; Muhammad Sabandi (Jurnal Pendidikan Indonesia, 2024)
The current problem is that the teaching profession is experiencing a professional and quantity crisis because it needs to attract young people to enter the teaching profession in the future. This research focuses on economics education students who are expected to become teachers in the future. This study aims to examine the effect of motivation to become a teacher on altruism. In conducting this study, a survey of 230 education students at two universities of education in Indonesia who are completing a four-year undergraduate program to become secondary school teachers was conducted. The research method used was a quantitative survey. The data collection method used was a questionnaire. Data processing was done by hierarchical regression. The results found in this study indicate that motivation to become a teacher has a positive and significant influence on altruism. Female students tend to be more motivated to become teachers than male students. The findings of this study prove that gender can moderate the relationship between altruism and motivation to become a teacher, while culture is a quasi-moderation revealed in this study.